2019
DOI: 10.1149/09101.1985ecst
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Impedance Analysis of Ni/CGO10-Based Electrolyte-Supported Cells

Abstract: To obtain a better understanding of the behavior of Ni/CGO fuel electrodes, this work presents a comprehensive investigation of Ni/CGO10-based electrolyte-supported cells. Commercial Ni/CGO10|CGO10|3YSZ|CGO10|Ni/CGO10-based symmetrical cells were characterized between 550 -975 °C at pH 2 = 0.8 bar and pH 2 O = 0.2 bar and for different H 2 /H 2 O gas mixtures at 550 °C. Small electrode area, thin anodes and large gas flow rates were used to minimize mass transport contributions. The distribution of relaxation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…This behavior is very similar to that described by Riegraf et al. for Ni–GDC electrodes, although the origin of the different slopes is still under debate 29 . However, the similarity indicates that the electrode response is dominated by the Ni–GDC electrode, although the investigated cells in our work have additional gas diffusion impedance from the support that overlaps with the impedance of the Ni–GDC anode.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This behavior is very similar to that described by Riegraf et al. for Ni–GDC electrodes, although the origin of the different slopes is still under debate 29 . However, the similarity indicates that the electrode response is dominated by the Ni–GDC electrode, although the investigated cells in our work have additional gas diffusion impedance from the support that overlaps with the impedance of the Ni–GDC anode.…”
Section: Resultssupporting
confidence: 89%
“…BSD, backscattered electron detector; SEM, scanning electron microscopy under debate. 29 However, the similarity indicates that the electrode response is dominated by the Ni-GDC electrode, although the investigated cells in our work have additional gas diffusion impedance from the support that overlaps with the impedance of the Ni-GDC anode. As can be seen in the distribution of relaxation time in Figure S2, the peak at the lowest frequency shows clear temperature dependence, meaning that gas diffusion in the support (which shows hardly any temperature dependence) is not the only cause of this peak.…”
Section: Single-cell Performancementioning
confidence: 65%
“…Similarly, it also can be observed that the MPD value of Cycle 6 is slightly lower than the MPD of Cycle 5. Anode conductivity in Cycle 4 coating may have been increased greatly by the reduction of Ce(IV) into Ce(III) as well in running conditions 39 . The high gas permeability of Cycle 4 has given the advantage to make the performance to be on par with the anode having low gas permeability but with high conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…ECS Transactions, 111 (6) 1431-1443 (2023) Riegraf et al have also published about the initial performance and long-term stability of electrolyte-supported (Ni-CGO fuel electrode) SoA cells (8). The reported resistance of low frequency processes at 850 °C (H2O/H2 20/80 %) is of 0.1 Ωcm 2 .…”
Section: Introductionmentioning
confidence: 99%